(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Ramanujacharya is a great scholar of South India and one of the six Vedantic Acharyas. He has an important contribution in philosophy. He equates knowledge and karma, giving equal importance to both. Therein lays the trauma. Yet for the common man it is useful and gives equal importance to both Karmmimamsa and Brahmimamsa. It has accepted the differences and similarities in it.